The Influence of Compositional Variations in Kecombrang (Etlingera elatior) Stem Fiber and Epoxy Resin on Impact Strength: Pengaruh Variasi Komposisi Serat Batang Kecombrang dan Resin Epoxy terhadap Ketahanan Impak - Syahri S; Ferri Safriwardy; Reza Putra; Muhammad; Nurul Islami (Malikussaleh Journal of Mechanical Science and Technology, 2025)
This research aims to evaluate the effect of variations in fiber type and volume fraction of torch ginger (kecombrang) stem fibers on the impact toughness of epoxy resin-based composite materials. The method used in the composite fabrication process was the Hand Lay-Up technique. Based on the test results using the Charpy Impact method, the first specimen—with a volume fraction composition of 70% torch ginger stem fiber and 30% epoxy resin—demonstrated the highest energy absorption capacity at 11.513 Joules. The second specimen, consisting of 65% torch ginger stem fiber and 35% epoxy resin, produced an energy absorption of 10.294 Joules, slightly lower than the first specimen. Meanwhile, the third specimen recorded the lowest energy absorption at 9.511 Joules with a composition of 60% torch ginger stem fiber and 40% epoxy resin, indicating that this specimen possesses the lowest impact toughness among the three tested configurations.